Clustering Vaksinasi Penyakit Mulut dan Kuku Menggunakan Algoritma K-Means - Adrian Maulana; Alwis Nazir; Reski Mai Candra; Suwanto Sanjaya; Fadhilah Syafria (Journal of Information System Research (JOSH), 2023)
Foot and Mouth Disease (FMD) is a viral infectious disease that is acute and highly contagious in artiofactyl or even-toed hoofed animals. This disease is caused by tyoe A virus forum picornaviridae, genus Apthovirus namely Aphtaee epizootecae. This disease has a development period of 1-14 days since the infected animal. The defense of this virus is quite strong and survives in glands, milk bones and milk products. The morbidity rate is up to 100% and mortality is high in infected young animals. Areas with the highest transmission of foot and mouth disease are areas with high livestock density, so stricter biosecurity and animal traffic control must be implemented to prevent the disease. The problem in the Departement of Livestock and Animal Health of Riau Province is the difficulty in categorizing food and mouth disease vaccination data of which regions have done the first and second vaccine specifically for cattle in Riau Province. Therefore, this study will categorizing the first and sceond vaccine eith high immunity using K-Means algorithm. Parameter used are vaccination status, breed, gender and age. By applying the K-Means algorithm, two clusters are formed, namely the cluster with high immunity of 21232 cows, and the cluster with low immunity 48704 cows. Testing with DBI with K=2 produces a value of 0.416.